Effect of Bispyribac-Sodium and Spacing on The Weed Control and Performance of Aromatic Rice Varieties (Bangladesh Agronomy Journal, 2024)
Rice (Oryza sativa L.), a staple grain, serves as a fundamental dietary component for billions by providing carbohydrates, vitamins, and minerals, supporting livelihoods, and stimulating national economies. A field experiment was led from July to December 2019 at the Sher-e-Bangla Agricultural University’s agronomy field in Dhaka, Bangladesh, to determine how a post-emergent herbicide and spacing impacts aromatic rice varieties' growth, yield, and weed control. The investigation consisted of three factors, i.e., weed control treatments: weedy check (no weeding) and Bispyribac-sodium WP @ 150 g ha−1, aromatic rice varieties: Kalizira and BRRI dhan37 and spacing: 20 cm × 15 cm, 25 cm × 15 cm, 20 cm × 20 cm, and 25 cm × 25 cm in a split-split plot design with three replications. Thirteen dissimilar types of weeds invaded the experimental plots. Among them, Monochoria vaginalis was the most prevalent weed at 30 and 60 DAT (24.67 and 19.67 weed population m−2 and 15.24 and 13.02% relative weed density sequentially). Among all the factors, the application of Bispyribacsodium WP (W1), BRRI dhan47 (V2, grain yield 2.99 t ha−1) and 20 cm × 20 cm (S3, grain yield 2.87 t ha−1) spacing provided promising results. According to the findings, BRRI dhan37 planted at 20 cm × 20 cm spacing, along with the suggested application of Bispyribac-sodium WP could provide the best result.Bangladesh Agron. J. 2024, 26(2): 56-66